Advancing digital health applications: priorities for innovation in real-world evidence generation - Stern, Ariel D.; Brönneke, Jan; Debatin, Jörg F.; Hagen, Julia; Matthies, Henrik; Patel, Smit; Clay, Ieuan; Eskofier, Björn; Herr, Annika; Hoeller, Kurt; Jaksa, Ashley; Kramer, Daniel B.; et al. (The Lancet Digital Health, 2022)
In 2019, Germany passed the Digital Healthcare Act, which, among other things, created a “Fast-Track” regulatory and reimbursement pathway for digital health applications in the German market. The pathway explicitly provides for flexibility in how researchers can present evidence for new digital products, including the use of real-world data and real-world evidence. Against this backdrop, the Digital Medicine Society and the Health Innovation Hub of the German Federal Ministry of Health convened a set of roundtable discussions to bring together international experts in evidence generation for digital medicine products. This Viewpoint highlights findings from these discussions with the aims of (1) accelerating and stimulating innovative approaches to digital medical product evaluation, and (2) promoting international harmonisation of best evidentiary practices. Advancing these topics and fostering international agreement on evaluation approaches will be vital to the safe, effective, and evidence-based deployment and acceptance of digital health applications globally.
CRIS-Team Scopus Importer:2022-03-04

Diagnosis Related Payment for Inpatient Mental Health Care: Hospital Selection and Effects on Length of Stay - Tauchmann, Harald; Reif, Simon; Valder, Franziska (Health Economics, 2025)
We study a policy introducing diagnosis related payment for inpatient mental health care in Germany with rates decreasing over length of stay. Using data on all hospital cases, we first examine which hospitals voluntarily opt into the new scheme. We show that specialized hospitals that treat more complicated cases and are reimbursed more highly under the new scheme select into it. Second, we study the effect of diagnosis related payment on length of stay. We find that diagnosis related payment is associated with large reductions in length of stay but has no effect on mortality, post-acute care, or the ambulatory sector. We argue that the reductions in length of stay are driven by the fact that diagnoses related reimbursement is higher for more complex cases and by payment decreasing over length of stay. This novel evidence contributes to a scarce literature on the role of payment systems for inpatient mental health care and provides important insights for policymakers
Keywords: Mental health care; Provider payment; Policy evaluation; DiD

Dynamic HTA for digital health solutions: opportunities and challenges for patient-centered evaluation - Brönneke, Jan B.; Herr, Annika; Reif, Simon; Stern, Ariel D. (International Journal of Technology Assessment in Health Care, 2023)
OBJECTIVES: Germany's 2019 Digital Healthcare Act (Digitale-Versorgung-Gesetz, or DVG) created a number of opportunities for the digital transformation of the healthcare delivery system. Key among these was the creation of a reimbursement pathway for patient-centered digital health applications (digitale Gesundheitsanwendungen, or DiGA). Worldwide, this is the first structured pathway for "prescribable" health applications at scale. As of October 10, 2023, 49 DiGA were listed in the official directory maintained by Germany's Federal Institute for Drugs and Medical Devices (BfArM); these are prescribable by physicians and psychotherapists and reimbursed by the German statutory health insurance system for all its 73 million beneficiaries. Looking ahead, a major challenge facing DiGA manufacturers will be the generation of the evidence required for ongoing price negotiations and reimbursement. Current health technology assessment (HTA) methods will need to be adapted for DiGA. METHODS: We describe the core issues that distinguish HTA in this setting: (i) explicit allowance for more flexible research designs, (ii) the nature of initial evidence generation, which can be delivered (in its final form) up to one year after becoming reimbursable, and (iii) the dynamic nature of both product development and product evaluation. We present the digital health applications in the German DiGA scheme as a case study and highlight the role of RWE in the successful evaluation of DiGA on an ongoing basis. RESULTS: When a DiGA is likely to be updated and assessed regularly, full-scale RCTs are infeasible; we therefore make the case for using real-world data and real-world evidence (RWE) for dynamic HTAs. CONCLUSIONS: Continous evaluation using RWD is a regulatory innovation that can help improve the quality of DiGAs on the market.
CRIS-Team Scopus Importer:2023-12-15
Keywords: biomedical technology assessment; digital health; Germany; government regulation; medical economics; reimbursement; software

Gesundheitsdaten: Von Nachbarländern lernen - Fischer, Martin; Jürges, Hendrik; Mangelsdorf, Stefan; Reif, Simon; Ullrich, Hannes; Wuppermann, Amelie (Wirtschaftsdienst, 2023)
The access and use of administrative health data in Germany is limited by several factors. Due to the large number and heterogeneity of data holders, data are usually only available in fragmented form, and access is often regulated in a non-transparent manner. Linkage of health data with other data sources is hardly possible for legal and logistic reasons. These limitations directly affect the ability of researchers in Germany to supply evidence-based policy advice and to conduct fundamental research. Against the backdrop of neighbouring countries, such as Denmark or Austria, giving access to and allowing the linkage of individual administrative data, we propose several measures to improve access to health data in Germany.
Created from Fastlane, Scopus look-up

Health Effects of Instruction Intensity Evidence from a Natural Experiment in German High-Schools - Quis, Johanna Sophie; Reif, Simon (2017)
A large literature aims to establish a causal link between education and health using changes in compulsory schooling laws. It is however unclear how well more education is operationalized by marginal increases in school years. We shed a new light on this discussion by analyzing the health effects of a reform in Germany where total years of schooling for students in the academic track were reduced from nine to eight while keeping cumulative teaching hours constant by increasing instruction intensity. e sequential introduction of the reform allows us to implement a triple difference-in-differences estima- tion strategy with data from the German Socio-Economic Panel. We nd that increased weekly instruction time has negative health effects for females while they are still in school. However, aer graduation, females even seem to beneffit from reduced school years. We find no effects on males’ healths.
Keywords: education and health; instruction intensity; natural experiment; SOEP

Hospital capacity reporting in Germany during Covid-19 - Reif, Simon; Schubert, Sabrina (Journal of Economic Behavior & Organization, 2024)
During the COVID-19 pandemic, hospitals faced a unique predicament. Hospital care was urgently needed and society took efforts to prevent overwhelming hospitals. However, hospitals in case-based reimbursement schemes faced financial problems because of canceled elective care visits and government regulations to keep capacity free for Covid-19 patients. Therefore, emergency financing measures were implemented in many countries. We analyze how hospitals in Germany responded to a scheme that provided financial support if the intensive care unit (ICU) occupancy rate in a county exceeded 75%. The scheme distributed over seven billion euros to hospitals and was notable because financial support depended on a measure (ICU occupancy rate) that hospitals could directly influence. To analyze hospitals’ reactions to this scheme, we employ event study analyses comparing ICU capacity before and after regions became eligible. We find no evidence of strategic reporting at an economically meaningful and hence empirically detectable scale.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Covid; Financial support programs; Hospitals; Misreporting

Increased instruction time and stress-related health problems among school children - Marcus, Jan; Reif, Simon; Wuppermann, Amelie; Rouche, Amélie (Journal of Health Economics, 2020)
While several studies suggest that stress-related mental health problems among school children are related to specific elements of schooling, empirical evidence on this causal relationship is scarce. We examine a German schooling reform that increased weekly instruction time and study its effects on stress-related outpatient diagnoses from the universe of health claims data of the German Social Health Insurance. Exploiting the differential timing in the reform implementation across states, we show that the reform slightly increased stress-related health problems among school children. While increasing instruction time might increase student performance, it might have adverse effects in terms of additional stress.
CRIS-Team Scopus Importer:2020-02-07
Keywords: G8 reform; Instruction time; Mental health; Stress

In sickness and in health? Health shocks and relationship breakdown: Empirical evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (Journal of Economic Behavior & Organization, 2021)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship. </
Keywords: Separation; Partnership dissolution; Health shock; MCS; PCS; Matching; Gender

In sickness and in health? Health shocks and relationship breakdown: Empirical evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (Journal of Economic Behavior & Organization, 2021)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Health shock; Matching; MCS; Partnership dissolution; PCS; Separation

In Sickness an in Health? Health Shocks and Relationship Breakdown: Empirical Evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (2019)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship.<br
Keywords: separation; partnership dissolution; health shock; MCS; PCS; matching

Is it good to be too light? Birth weight thresholds in hospital reimbursement systems - Reif, Simon; Wichert, S.; Wuppermann, A. (Journal of Health Economics, 2018)
Birth weight manipulation has been documented in per-case hospital reimbursement systems, in which hospitals receive more money for otherwise equal newborns with birth weight just below compared to just above specific birth weight thresholds. As hospitals receive more money for cases with weight below the thresholds, having a (reported) weight below a threshold could benefit the newborn. Also, these reimbursement thresholds overlap with diagnostic thresholds that have been shown to affect the quantity and quality of care that newborns receive. Based on the universe of hospital births in Germany from the years 2005–2011, we investigate whether weight below reimbursement relevant thresholds triggers different quantity and quality of care. We find that this is not the case, suggesting that hospitals’ financial incentives with respect to birth weight do not directly impact the care that newborns receiv

Is it good to be too light? Birth weight thresholds in hospital reimbursement systems - Reif, Simon; Wichert, S.; Wuppermann, A. (2017)

Physician behavior under prospective payment schemes: Evidence from artefactual field and lab experiments - Hafner, Lucas; Reif, Simon; Seebauer, Michael (2017)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party representing the health insurance which finances medical service provision. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical services. We conduct a laboratory experiment in neutral as well as medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.<br
Keywords: health economic experiment; framing; physician behavior; prospective payment schemes

Physician behavior under prospective payment schemes—evidence from artefactual field and lab experiments - Reif, Simon; Hafner, Lucas; Seebauer, Michael (International Journal of Environmental Research and Public Health, 2020)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party which represents the health insurance that finances medical service provision under a prospective payment scheme. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical care. We conduct a laboratory experiment in neutral as well as in medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly and are more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Framing; Health economic experiment; Physician behavior; Prospective payment schemes

Poly Implant Prothèse and Rofil Substandard Breast Implant Explantations from a Large German Single Centre from 2011 to 2014: A Comparative Study - Billner, Moritz; Wirthmann, Anna; Reif, Simon; Rieger, Ulrich (Aesthetic Plastic Surgery, 2016)
Background Following a Europe-wide scandal, substandard breast implants containing silicone for industry purposes produced by Poly Implant Prothèse (PIP&Rofil) were explanted due to its potential health risks. Objective We investigated whether these implants actually imposed a threat to patients’ health. Methods In this retrospective single-centre case–control study, we compared patients with breast augmentation receiving implant explantation (01/2011–01/2015). Data were collected retrospectively from the patients’ records. Patients were split into two groups: PIP&Rofil and implants of other manufacturers. Results A total of 307 patients with 495 breast implants met the inclusion criteria, 64 patients with 115 PIP&Rofil implants and 243 patients with 380 implants of other manufacturers. Comparison of descriptive statistics between the two groups revealed that for a variety of indicators (e.g. patient age, breast cancer, aesthetic vs. reconstructive indication, implant volume, submuscular vs. subglandular implant position) PIP implants differ from non-PIP implant patients. Raw mean comparison showed higher rupture rates for non-PIP implants, 28.42 % (PIP 23.48 %). However, when controlling for implant indwelling time, PIP implants had shown higher rupture rates. Both groups had similar rates of capsular contracture (PIP: 71.30 %, Others: 72.63 %) with different distribution of Baker Scores (Baker 2/3/4: PIP 5/8/13 and non-PIP 3/24/135). Conclusion Concerning patient symptoms, we did not find any objective reason to justify implant explantation of PIP&Rofil implants as a solely precautionary measure. As PIP&Rofil implants showed shorter retention periods until rupture and ruptured implants can cause symptoms or health problems, PIP&Rofil implants should be regularly monitored and explanted if there is evidence of rupture
Keywords: PIP implants Silicone Breast implants Implant rupture Clinical findings Capsular contracture

Poly Implant Prothèse and Rofil Substandard Breast Implant Explantations from a Large German Single Centre from 2011 to 2014: A Comparative Study - Billner, Moritz; Wirthmann, Anna; Reif, Simon; Rieger, Ulrich M. (Aesthetic Plastic Surgery, 2016)
Background Following a Europe-wide scandal, substandard breast implants containing silicone for industry purposes produced by Poly Implant Prothèse (PIP&Rofil) were explanted due to its potential health risks. Objective We investigated whether these implants actually imposed a threat to patients’ health. Methods In this retrospective single-centre case–control study, we compared patients with breast augmentation receiving implant explantation (01/2011–01/2015). Data were collected retrospectively from the patients’ records. Patients were split into two groups: PIP&Rofil and implants of other manufacturers. Results A total of 307 patients with 495 breast implants met the inclusion criteria, 64 patients with 115 PIP&Rofil implants and 243 patients with 380 implants of other manufacturers. Comparison of descriptive statistics between the two groups revealed that for a variety of indicators (e.g. patient age, breast cancer, aesthetic vs. reconstructive indication, implant volume, submuscular vs. subglandular implant position) PIP implants differ from non-PIP implant patients. Raw mean comparison showed higher rupture rates for non-PIP implants, 28.42 % (PIP 23.48 %). However, when controlling for implant indwelling time, PIP implants had shown higher rupture rates. Both groups had similar rates of capsular contracture (PIP: 71.30 %, Others: 72.63 %) with different distribution of Baker Scores (Baker 2/3/4: PIP 5/8/13 and non-PIP 3/24/135). Conclusion Concerning patient symptoms, we did not find any objective reason to justify implant explantation of PIP&Rofil implants as a solely precautionary measure. As PIP&Rofil implants showed shorter retention periods until rupture and ruptured implants can cause symptoms or health problems, PIP&Rofil implants should be regularly monitored and explanted if there is evidence of rupture.

Produktivitätsparadoxon der Digitalisierung im Krankenhaus – auf der Suche nach effizienzsteigernden Innovationen - Reif, Simon; Bolz, Theresa; Karamik, Yasemin (Wirtschaftsdienst, 2024)
The productivity paradox of digitisation in hospitals refers to the difficulty in realising measurable efficiency gains from digital innovations. Despite significant investments, healthcare costs continue to rise, particularly in OECD countries like Germany. While digitisation is expected to enhance efficiency, empirical evidence for substantial productivity improvements remains limited. This study analyses data from the European Hospital Survey and finds no clear correlation between hospitals' digital integration and operational efficiency. It remains uncertain whether current policy efforts to increase health care digitalisation will yield the desired efficiency gains. More robust evidence to identify innovations that genuinely improve healthcare efficiency is needed to avoid cuts to available care for individuals in the social health insurance.
Created from Fastlane, Scopus look-up
Keywords: I11; I18; O33

Setting incentives right with long-term risk adjustment - Reif, Simon; Schubert, Sabrina; Wambach, Achim (European Journal of Health Economics, 2024)
CRIS-Team Scopus Importer:2025-02-04

The effect of self-inflicted burns on ABSI score prediction power: A four-year prospective multicenter study of the German Burn Registry - Billner, Moritz; Reif, Simon; Registry, German Burn; Reichert, Bert (Burns, 2022)
Background: Suicide attempted by self-inflicted burns are associated with lower survival rates compared to accident related burns. Objective: We investigate the relation between self-inflicted burns (SIB) and survival rates and how this relation is moderated by variables used to predict survival rates in the ABSI score, a widely used measure. Additionally, we compare the predicted survival rates by the ABSI score to the actual rates in our sample for SIB and accident patients. Methods: In this prospective multicenter study data from the German Burn Registry are statistically analyzed using two sided t-test and multivariate linear regression models. Results: 5330 patients (214 with SIB) met our inclusion criteria. We find a 6.8 percentage points lower survival rate for patients with SIB when we control for patient condition with the five ABSI components as covariates. These higher mortality rates can be explained by the higher rate of therapy restrictions for patients with self-inflicted burns. Additionally, different ABSI modifications can improve the predictive power of the score. Conclusion: Patients with SIB have lower survival rates compared to accident patients. Recently proposed modifications of the ABSI score can improve the accuracy of survival rate prediction for SIB.
Created from Fastlane, Scopus look-up
Keywords: ABSI; Burn assessment; Mortality; Self-inflicted; Suicide

The prognostic relevance of full-thickness burns on ABSI - Gorenflo, J.; Reichert, Bert; Registry, German Burn; Reif, Simon; Megas, Ioannis Fivos; Billner, Moritz (Burns, 2024)
Introduction The Abbreviated Burn Severity Index (ABSI) by Tobiasen, which is commonly used to estimate the mortality risk of severely burned patients, calculates an additional point for the existence of full-thickness (third-degree) burns. [1] However, the score does not consider the extent of how much of the burnt body surface was affected by thirddegree burns. To understand whether there is a way to improve ABSI prediction power, this study aims to determine the influence of full-thickness burns on survival rates and how it affects the predictive precision of the ABSI. Material and methods In this study, the statistical evaluation of 2538 patients collected prospectively in the context of the German Burn Registry was carried out. A linear regression analysis was carried out to show the prognostic relevance of full-thickness burns. Age, sex, TBSA (Total Body Surface Area), and the presence of an inhalation injury were also observed as further influencing factors. Results Among the 2538 patients meeting our inclusion criteria, full-thickness burns were found in 1233 patients. In patients with a TBSA below 20 %, the extent of full-thickness burns is not relevant to the prognosis in terms of survival probability (p = 0.124). With more than 20 % TBSA, the extent of third-degree burns is of significant relevance (p = 0.000). In patients without full-thickness burns and calculated ABSI values ≥ 12 the survival rate of 46 % was noticeably better than the predicted survival rate of < 10 % according to the ABSI-Score, whereas the predicted survival rate in patients with third-degree burns (< 10 %), closely matched with the observed survival rate of 11 %. Conclusion For patients with a TBSA < 20 %, the presence of full-thickness burns is not relevant for survival. In contrast to this observation, the percentage of full-thickness burns is of crucial prognostic importance for patients with a TBSA of > 20 %. By adjusting the ABSI and taking into account the exact percentage of third-degree burns, an improvement in the prognostic precision of the score could be achieve
Keywords: ABSI; Full-thickness burns; Survival

Vorsorgelücke während der Coronavirus-Pandemie – Vorsorgeuntersuchungen in der Krise - Reif, Simon; Schubert, Sabrina (2021)